Caminhos e (des) caminhos na educação de surdos: da reabilitação à inclusão - Gobbi, Mirian (2006)
This research analyses the speeches referring to deaf people education. These speeches, in their constitution, were outlined through medical and educational understanding and they indicate a think way, of conceiving and acting about people with deafness. Such speeches are based in the necessity of putting these people in the society with the goal of improving the practices that initially were destined to rehabilitation, normalization and discipline of the deaf people; later the speeches moved out influenced by conceptions based in points that serch not only the integration of these people in the society, but the overcoming of the educational difficulties, expressed in the communications barriers and in limits in the pedagogical practices. This study analyses as the local public power in Uberlândia oriented the deaf people educational practices and as such practices were developed in Institutions that guided their works for attending of the deaf children, young people and adults. From this moment, were built speeches that became possible to notice and see these social people and the speeches also influenced straighstly in the pedagogical practices that were destined to rehabilitate and to normalize the deaf people and later include them educational and socially. The investigation also observes the experiences of a deaf group and searches to understand the senses they attribute at their social relations, as deaf people as listener people, the identification with the pairs, at the interest, at the dreams and at the perspectives that revealed a specific way of living of one deaf group in Uberlândia.